Spatially resolved upwelling in the California Current System and its connections to climate variability. Issue 9 (7th May 2014) - Jacox, M. G.; Moore, A. M.; Edwards, C. A.; Fiechter, J.
<x xml:space="preserve">Abstract</x> A historical analysis of California Current System (CCS) circulation, performed using the Regional Ocean Modeling System with four‐dimensional variational data assimilation, was used to study upwelling variability during the 1988–2010 period. We examined upwelling directly from the vertical velocity field, which elucidates important temporal and spatial variability not captured by traditional coastal upwelling indices. Through much of the CCS, upwelling within 50 km of the coast has increased, as reported elsewhere. However, from 50 to 200 km offshore, upwelling trends are negative and interannual variability is 180° out of phase with the nearshore signal. This cross‐shore pattern shows up as the primary mode of variability in central and northern CCS vertical velocity anomalies, accounting for ∼40% of the total variance. Corresponding time series of the dominant modes in the central and northern CCS are strongly correlated with large‐scale climate indices, suggesting that climate fluctuations may alternately favor different biological communities.